A Catalyst for Change: The European Cancer Patient's Bill of Rights. (3rd February 2014) - Lawler, Mark; Le Chevalier, Thierry; Murphy, Martin J.; Banks, Ian; Conte, Pierfranco; De Lorenzo, Francesco; Meunier, Françoise; Pinedo, H.M.; Selby, Peter; Armand, Jean-Pierre; Barbacid, Mariano; Barzach, Michèle; et al.
Abstract : The European Cancer Concord is a unique patient-centered partnership that will act as a catalyst to achieve improved access to an optimal standard of cancer care and research for European citizens. In order to provide tangible benefits for European cancer patients, the partnership proposes the creation of a "European Cancer Patient's Bill of Rights, " a patient charter that will underpin equitable access to an optimal standard of care for Europe's citizens.